Pengembangan Aplikasi Berbasis Konsep Smart Classroom Sebagai Sarana Pendukung Interaksi Pembelajaran - Hetty Meileni (MANAJEMEN INFORMATIKA, 2010)
Interaction has played important role in learning process. In general, learning interaction is demonstrated by open discussion in campus environment or by delivering conversation in classroom activities. Nowadays, learning interaction is supported by information technology. Information technology is adopted by many researchers through various concepts with the same purpose, i.e. change learning interaction into more collaborative and attractive learning experience for student. Smart Classroom is one of the concepts that describe the implementation of the Information technology used in educational environments, especially in learning process. Smart Classroom itself is a part of research Intelligent Environment. It demonstrates an Information technology environment combined the involvement of teachers and students in learning process. Many scenarios of smart classroom concept have been implemented with the help of existing tools. The tools could be software or hardware that is integrated into single environment. In this research, researcher tried to develop an application based on Smart Classroom concept. In contrast with previous research, this research provides an application where participants will be able to deal with Smart Classroom solution in single package software without any need for additional hardware.